2019
DOI: 10.1186/s13287-019-1327-5
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of human umbilical cord mesenchymal stem cell-derived microvesicles on premature ovarian insufficiency in mice

Abstract: Background Premature ovarian insufficiency (POI) is one of the leading causes of female infertility, which is caused by an abnormal ovarian reserve. Currently, there is no effective treatment to restore the fertility of POI patients. Recent studies suggested that microvesicles (MVs) released from mesenchymal stem cells (MSCs) exert therapeutic effects in various degenerative diseases. In this study, the effect of human umbilical cord MSC-derived MVs (HUCMSC-MVs) on the restoration of ovarian funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(63 citation statements)
references
References 44 publications
4
49
1
1
Order By: Relevance
“…Consistent with our findings, hUMSCs and hUMSC-Exos have been reported to preserve ovarian function in POI mice. 12,15,18,20 Previous studies have also reported that exosomes from human adipose MSCs and amniotic fluid stem cells can restore ovarian function after CTX-induced damage. 18,20 In addition, the expression levels of SIRT7 and its candidate downstream target genes were downregulated after hUMSC-Exos treatment in this study.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Consistent with our findings, hUMSCs and hUMSC-Exos have been reported to preserve ovarian function in POI mice. 12,15,18,20 Previous studies have also reported that exosomes from human adipose MSCs and amniotic fluid stem cells can restore ovarian function after CTX-induced damage. 18,20 In addition, the expression levels of SIRT7 and its candidate downstream target genes were downregulated after hUMSC-Exos treatment in this study.…”
Section: Discussionmentioning
confidence: 98%
“…12,13 One of the key mechanisms of MSC-induced therapeutic effects is the paracrine activity of secreted factors, which are mediated by extracellular vesicles (EVs). 10,14,15 Among the many subtypes of EVs, exosomes are considered to be powerful cell-to-cell communicationrelevant components of the MSC secretome with low immunogenicity and tumorigenicity. 16,17 Exosomes released from hUMSCs (hUMSC-Exos) are reported to suppress ovarian granulosa cell apoptosis and regulate the immune response.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, EVs contain a subset of proteins, lipids, and nucleic acids derived from the donor cell and play important roles in intercellular communication through transferring their contents, including proteins, lipids, and RNAs, between cells [13]. EVs produced by MSCs (MSC-EVs) exert therapeutic effects in several disease models such as chemotherapy-induced mouse model of premature ovarian failure [14], experimental allergic asthma [15], and Escherichia coli endotoxin-induced acute lung injury [16]. In addition, EVs have reduced potential side effects because they are less complex and better defined as compared to MSC therapies, and there are additional logistical advantages of using EVs, which can be considered as an off-the-shelf product.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, previous studies evaluate the safety of human umbilical cord mesenchymal stem cells (HUCMSCs) derived EVs on liver or renal function 14 , but no study investigates whether the treatment of EVs to women of child-bearing age will influence the development of their offspring. Recently, Yang et al 15 found that EVs derived from HUCMSCs could locate in ovarian tissue after transplantation and play essential roles in promoting ovarian angiogenesis and restoring ovarian function of POI mice. However, they neither evaluate the fertility of the POI mice nor the influence on their offspring after EVs transplantation, which is of great concern for a new treatment for women with POI who desire to have a child.…”
Section: Introductionmentioning
confidence: 99%